Management of prescribed pharmacotherapeutic care: A strategy to minimize the impact of drug shortages in times of scarcity in the COVID-19 pandemic - Martins , Bruna Cristina Cardoso; Rebouças, Karynne Miranda; Carvalho , Alyne Mara Rodrigues de; Teixeira, José Emídio Rocha; Severino, Rafaela Neres; Oliveira, Jefferson Silva (Seven Editora, 2023)
The lack of medication shortages is considered a public health problem and represents an obstacle to ensuring access to pharmacotherapeutic treatment for patients. For episodes of shortages to be minimized and for the hospitalized patient to receive treatment, management strategies should be developed. The present study aims to describe the management of an indicator that monitors the care of the pharmacotherapeutic treatment prescribed to patients admitted to a hospital. This is an observational, descriptive, cross-sectional, and retrospective study on the management of pharmacy care indicators of the pharmacotherapeutic treatment prescribed to patients hospitalized in a public hospital in Fortaleza/Ceará. The indicator was implemented in May/2020 with consolidation and systematic management of its data from June/2020. A total of 334,114 prescriptions were met, and 32,658 were missing. The acceptance rate of pharmaceutical interventions related to supply in June/2020: was 54.3% and in May/2022: 100% (average: 90% ±11%). During the indicator: 0% rupture of class Z drugs (immediate impact and no substitute); 2% of class Y drugs (immediate impact and with substitute) and 98% of the drugs were class X (no immediate impact and more than one substitute). Daily monitoring is performed according to the XYZ curve, evaluating coverage time and purchases in progress. The management of an indicator to evaluate the attendance of the prescribed pharmacotherapeutic treatment with real-time decision-making, aligning logistics and clinic, made it possible to minimize the shortage of medicines in the COVID-19 pandemic and the current shortage of market input. DOI:https://doi.org/10.56238/emerrelcovid19-068